Hair cortisol as a neuroendocrine biomarker to evaluate the impact of chronic stress on the interaction between neuropsychiatric disorders and metabolic syndrome - Van den Heuvel, Leigh Luella (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.